Optomechanic interactions in phoxonic cavities - Bahram Djafari-Rouhani; Said El-Jallal; Mourad Oudich; Yan Pennec (AIP Advances, 2014)
Phoxonic crystals are periodic structures exhibiting simultaneous phononic and photonic band gaps, thus allowing the confinement of both excitations in the same cavity. The phonon-photon interaction can be enhanced due to the overlap of both waves in the cavity. In this paper, we discuss some of our recent theoretical works on the strength of the optomechanic coupling, based on both photoelastic and moving interfaces mechanisms, in different (2D, slabs, strips) phoxonic crystals cavities. The cases of two-dimensional infinite and slab structures will enable us to mention the important role of the symmetry and degeneracy of the modes, as well as the role of the materials whose photoelastic constants can be wavelength dependent. Depending on the phonon-photon pair, the photoelastic and moving interface mechanisms can contribute in phase or out-of-phase. Then, the main part of the paper will be devoted to the optomechanic interaction in a corrugated nanobeam waveguide exhibiting dual phononic/photonic band gaps. Such structures can provide photonic modes with very high quality factor, high frequency phononic modes of a few GHz inside a gap and optomechanical coupling rate reaching a few MHz.